PENGARUH ELISITOR Al3+ TERHADAP AKUMULASI DAIDZEIN DAN GENISTEIN PADA KALUS Phaseolus vulgaris L. Dan Phaseolus aureus Roxb. - S. K. Dewi; W. Widoretno; Warsito Warsito (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
The Estrogen was very beneficial hormone for men and women. Isoflavon compound was natural estrogen source which contain three main compound in chemical form, the aglycones, daidzein and genistein. They were found only 0,25% on plant, exclusively on leguminous plant. An alternative method have been required to overcome these problem, for example, through plant cell culture technic with heavy metal elicitor. The aims of this research were to study the effect of various concentration of Al3+ elicitor and age of culture for callus growth and accumulation of daidzein and genistein from in vitro Phaseolus vulgaris L. And Phaseolus aureus Roxb callus culture. Stable plant callus culture were established and subculture for three times approximately 4 weeks. The calli were elicitated by Al3+ elicitor with 0, 50, 150, 300 µM concentrations and incubated on 4, 6, and 8 weeks. Qualitative data were determined based in changed calli colour, TLC plate and value of Rf. Quantitative data were determined based in fresh and dry weight of the calli and the content of daidzein and genistein compound. Quantitative data were analized using Anova and continued with DMRT 95%. The results showed that the callus growth more influenced by age of culture. The sixth weeks led to higher fresh and dry weight. The Colour of Calli had been changed from white yellowness become brown at the eighth weeks. The texture of Calli have no difference between control and treatment of elicitor, that was friable until the end of treatment. The Calli with addition of elicitor Al3+ with 150 µM concentrations had significantly highest of fresh weight than control, they were over 0,463 g. The Content of daidzein and genistein on Phaseolus vulgaris L. had significantly increased in addition of Al3+ elicitor with 150 µM concentration. But, the content of daidzein and genistein on Phaseolus aureus Roxb. had significantly increased in addition of Al3+ elicitor with 300 µM concentration. Keywords: Phaseolus vulgaris L., Phaseolus aureus Roxb., elicitor Al3+, Daidzein, Genistein, Callus Growth.